PERAN STAKEHOLDER DALAM PROGRAM PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA DI KOTA SEMARANG - Elista, Amanda; Kismartini, Kismartini; Rahman, Amni Zarkasyi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The high number of domestic violence in the city of Semarang is a problem that must be dealt with immediately. This is because domestic violence is the most common type of violence in Semarang from 2016-2020. In order to prevent the increasing number of domestic violence, the role of various government stakeholders, public and private institutions is needed. The implementation of these roles consists of roles as policy creator, coordinator, facilitator, implementor & accelerator. The method in this research is descriptive qualitative with data collection techniques through interviews and documentation. Determination of the subject using purposive sampling, data quality using source triangulation. The results of the research show that the implementation of the role of stakeholders has been running quite well, but it is not optimal, this can be seen from the discovery of problems 1) the high number of domestic violence in Semarang 2) lack of community commitment & DP3A to prevent domestic violence 3) lack of funds in carrying out socialization at below level. The results of the identification of stakeholders are divided into a) government stakeholders who carry out the roles of policy creator, coordinator, facilitator & implementor. In carrying out this role, it was found that the cause of the high number of domestic violence was due to economic factors, patriarchal culture, Semarang City as a complex city. b) community institutional stakeholders as facilitators & implementors found the cause of the high number of domestic violence due to the awareness factor of Semarang City residents to report c) private stakeholders as accelerators have carried out their roles well through CSR. The advice given is to strengthen mutual commitment between stakeholders, APSAI through corporate CSR can channel funds to other stakeholders who lack funds to carry out the program, the still high number of domestic violence can be suppressed by digital economic training, build a gender fair perspective, encourage the community to be brave to report accompanied by fast & appropriate handling, building awareness of Semarang City residents to care about domestic violence issues.